Towards an explanation of Irish rural-based social enterprises. Issue 2 (3rd May 2016) - O'Shaughnessy, Mary; O'Hara, Patricia
ABSTRACT: In Ireland social enterprises are seen primarily as non-profit organisations driven by social objectives. This article presents qualitative data gathered through a series of in depth interviews with representatives from five rural-based Irish social enterprises. The objectives of the article are to provide short descriptions of these social enterprises, to assess the critical success factors and barriers facing them, to discuss their potential for replication in other rural areas and some of the lessons to be learned from these initiatives.